High-sensitive troponin is associated with subclinical imaging biosignature of inflammatory cardiovascular involvement in systemic lupus erythematosus. Issue 11 (4th August 2018) - Winau, Lea; Hinojar Baydes, Rocio; Braner, Axel; Drott, Ulrich; Burkhardt, Harald; Sangle, Shirish; D'Cruz, David P; Carr-White, Gerry; Marber, Mike; Schnoes, Katrin; Arendt, Christophe; Klingel, Karin; et al.
Abstract : Background: Cardiovascular (CV) involvement in patients with systemic lupus erythematosus (SLE) is presumably subclinical for the major part of its evolution. We evaluated the associations between high-sensitive troponin T (hs-TropT), a sensitive marker of myocardial injury, and CV involvement using cardiac magnetic resonance (CMR). Methods and results: This is a two-centre (London and Frankfurt) CMR imaging study at 3.0 Tesla of consecutive 92 patients with SLE free of cardiac symptoms, undergoing screening for cardiac involvement. Venous samples were drawn and analysed post-hoc for cardiac biomarkers, including hs-TropT, high-sensitive C reactive protein and N-terminal pro brain natriuretic peptide. Compared with age-matched/gender-matched non-SLE controls (n=78), patients had significantly raised cardiac biomarker levels, native T1 and T2, aortic and ventricular stiffness, and reduced global longitudinal strain (p<0.01). In SLE, hs-TropT was significantly and independently associated with native T2, followed by the models including native T1 and aortic stiffness (Χ 2 0.462, p<0.01). There were no relationships between hs-TropT and age, gender, CV risk factors, duration of systemic disease, cardiac structure or function, or late gadolinium enhancement. Conclusions: Patients with SLE have a high prevalence of subclinical myocardial injury as demonstrated by raised high-sensitive troponin levels. CMR with T2 mapping reveals myocardial oedema as the strongest predictor of hs-TropT release, underscoring the inflammatory interstitial remodelling as the main mechanism of injury. Patients without active myocardial inflammation demonstrate diffuse interstitial remodelling and increased vascular stiffness. These findings substantiate the role of CMR in screening of subclinical cardiac involvement. Trial registration numer: NCT02407197 ; Results.